2020
DOI: 10.31838/jcr.07.05.183
|View full text |Cite
|
Sign up to set email alerts
|

Application of Iowa Model Evidence-Based Practice on Maternity Nurses Regarding Postpartum Hemorrhage

Abstract: The Iowa Model of Evidence-Based Practice give usguide line for nursing decisions to manage day-today practical work which haveeffect on patient healthbased on-solving problems through scientific procedures and recognized for its applicability's and usingthrough multidisciplinary healthcare teams. Aim of study was to apply Iowa model Evidence-Based practice on maternity Nurses regarding Postpartum Hemorrhage. Quasi study used in Obstetric and Genecology Hospital at Ain Shams Hospital. Seventy nurses were work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…This result comes in accordance with Baig et al [26], who studied Knowledge, Attitude, and Practices of Mid-Level Providers regarding Post Abortion Care in Sindh, Pakistan and reported that the studied nurses had limited knowledge regarding abortion and highlighted the need for providing comprehensive training and workshop to nurses regarding abortion. This result comes in line with El Sharkawy et al, [11] , who studied ''application of IOWA model evidence-based practice on maternity nurses regarding postpartum hemorrhage'' and reported that good knowledge regarding evidence-based practice was 4.3% preprogram compared by 81.4% post-program while regarding good postpartum knowledge equal 17.1% was increased to reach 71.4% post-program, and regarding total knowledge was 11.4% pre-program compared by 80.0% post-program and also showed highly statistically significant differences between nurses knowledge pre and post implementing evidence guidelines application. Regarding the relation between socio-demographic characteristics of the studied nurses and their total knowledge pre-evidence-based guideline application, the present study showed that there was a statistically significant relation between total knowledge levels of studied nurses' pre-evidence-based guideline application and their age and years of experience in which P-value ≤ 0.0009 & 0.0003 respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result comes in accordance with Baig et al [26], who studied Knowledge, Attitude, and Practices of Mid-Level Providers regarding Post Abortion Care in Sindh, Pakistan and reported that the studied nurses had limited knowledge regarding abortion and highlighted the need for providing comprehensive training and workshop to nurses regarding abortion. This result comes in line with El Sharkawy et al, [11] , who studied ''application of IOWA model evidence-based practice on maternity nurses regarding postpartum hemorrhage'' and reported that good knowledge regarding evidence-based practice was 4.3% preprogram compared by 81.4% post-program while regarding good postpartum knowledge equal 17.1% was increased to reach 71.4% post-program, and regarding total knowledge was 11.4% pre-program compared by 80.0% post-program and also showed highly statistically significant differences between nurses knowledge pre and post implementing evidence guidelines application. Regarding the relation between socio-demographic characteristics of the studied nurses and their total knowledge pre-evidence-based guideline application, the present study showed that there was a statistically significant relation between total knowledge levels of studied nurses' pre-evidence-based guideline application and their age and years of experience in which P-value ≤ 0.0009 & 0.0003 respectively.…”
Section: Discussionsupporting
confidence: 91%
“…This result agrees with Mahmoud [10] who studied knowledge of nurses about abortion in the women's hospital and obstetrics in the holy city of Karbala and General AL -Hindia Hospital and reported that nearly half of the age group to the study sample were within (20-24 year), three fourth of them have a nursing high school, the majority of them has (1-3) year of experience, and the major of the study sample wasn't share in training courses. This result is in the same line with El Sharkawy et al, [11]. who studied ''application of iowa model evidence-based practice on maternity nurses regarding postpartum hemorrhage'' and reported that most of the studied sample had no previous training courses.…”
Section: Discussionsupporting
confidence: 88%